ARTIFICIAL INTELLIGENCE (AI) IN ANSWERING ISLAMIC QUESTIONS FROM SHARIAH PERSPECTIVES (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
In Malaysia, the use of AI is not foreign at all because it has been introduced and used on a large scale in different fields, in fact, its capabilities can exceed those of ordinary humans. As we know, Artificial Intelligence (AI) is used in a variety of ways and is becoming an extremely important technology for everyone. The integration of artificial intelligence (AI) in Islam also raises intriguing questions and challenges. The purpose of the present study was to explore the definition of artificial intelligence (AI), and to examine whether the AI was permissible from Shariah perspectives. This study also discusses about the existing guidelines in other countries for the use of artificial intelligence in Islam. In this study, the author applies the qualitative research methodology by conducting a literature review, researching Islamic fatwas, and analyzing newspaper articles. The author will be analyzing and interpreting the information found in these sources to understand the perspectives, information, and opinions related to the topic research. As a result, research findings indicate that artificial intelligence (AI) provides significant benefits to humans in various aspect of life such as increased efficiency, improved quality of life, enhanced user experience, and increased accessibility. In Islam, there are many discussions regarding AI, which are some Islamic scholars and intellectuals have expressed their views on AI, with some seeing it as a useful tool in improving human life, while others have concerns about its potential negative impacts. Since there are various views related to the use of AI in answering Islamic questions, this study was conducted to determine the use of AI in answering Islamic questions from shariah perspectives.